Dryopteris × subdiffracta (Dryopteridaceae), a new natural hybrid fern from Guangxi, China - Hong-Jin Wei; Zheng-Yu Zuo (PhytoKeys)
A new natural hybrid fern, Dryopteris × subdiffracta (Dryopteridaceae), is reported from Guangxi, China. Molecular phylogenetic analysis based on DNA sequences from the low-copy nuclear marker Ak1 and plastid genome revealed respectively that D. polita and D. diffracta are parents of the new hybrid, with D. polita as the maternal parent. Cytometric analysis of the nuclear DNA content indicated that D. × subdiffracta might be a diploid hybrid. Morphologically, D. × subdiffracta shares a high degree of similarity with D. × subreflexipinna from Taiwan, especially in zigzag-shaped rachis and deflexed pinna stalks. However, D. × subdiffracta is distinguishable in the degree of lamina division and shapes of lamina and pinnulets. A comprehensive taxonomic description accompanied by line drawings are provided.